2012
DOI: 10.1158/1078-0432.ccr-12-1532
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms of Activity of the TORC1 Inhibitor Everolimus in Waldenstrom Macroglobulinemia

Abstract: Purpose: The TORC1 inhibitor everolimus has previously shown significant activity as a single agent in hematologic malignancies, with reported responses of 30% to 70% in Waldenstrom macroglobulinemia. However, the specific mechanisms by which this class of mTOR inhibitors exerts antiWaldenstrom macroglobulinemia activity have not been fully investigated. We therefore sought to dissect the mechanisms of everolimus-dependent modulation of Waldenstrom macroglobulinemia cell survival.Experimental Design: We confir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Firstly, suppression of the mTOR pathway by mir-100 enhanced the chemotherapeutic effect of rapamycin analog RAD001 (everolimus) in clear cell ovarian cancer cells [154]. Furthermore, knocking down miRNA-155 expression in low-grade lymphoma, Waldenström macroglobulinemia cells was shown to partially inhibit everolimus-dependent induction of toxicity [170]. This finding indicates that miRNA-155 could be a target responsible for the everolimus-induced anti-Waldenström macroglobulinemia effect [170].…”
Section: Combination Of Mirnas and Chemical Inhibitors To Target Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, suppression of the mTOR pathway by mir-100 enhanced the chemotherapeutic effect of rapamycin analog RAD001 (everolimus) in clear cell ovarian cancer cells [154]. Furthermore, knocking down miRNA-155 expression in low-grade lymphoma, Waldenström macroglobulinemia cells was shown to partially inhibit everolimus-dependent induction of toxicity [170]. This finding indicates that miRNA-155 could be a target responsible for the everolimus-induced anti-Waldenström macroglobulinemia effect [170].…”
Section: Combination Of Mirnas and Chemical Inhibitors To Target Tmentioning
confidence: 99%
“…Furthermore, knocking down miRNA-155 expression in low-grade lymphoma, Waldenström macroglobulinemia cells was shown to partially inhibit everolimus-dependent induction of toxicity [170]. This finding indicates that miRNA-155 could be a target responsible for the everolimus-induced anti-Waldenström macroglobulinemia effect [170]. In addition, another rapamycin analogue, CCI-779 (temsirolimus), shows increased anti-proliferative effects in miR-101 negative anaplastic lymphoma kinase (ALK) + large-cell lymphoma (ALCL) cells compared to ALK − cells [155].…”
Section: Combination Of Mirnas and Chemical Inhibitors To Target Tmentioning
confidence: 99%
“…In addition, we, and others have shown that miR155 is upregulated in WM and can also lead to activation of the PI3K pathway . Therefore, this pathway is highly activated in patients with WM .…”
Section: Introductionmentioning
confidence: 66%
“…Significant advances have emerged in the understanding of the pathogenesis of WM in the last few years. Recent studies using whole genome sequencing as well as epigenetic studies have shown that the PI3K/mTOR pathway is highly activated in WM, possibly due to MYD88 mutation or miRNA‐155 activation . These results indicate that this rare lymphoplasmacytic lymphoma is dependent to the PI3K/mTOR pathway, despite the lack of specific mutations in the pathway itself.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation